PENANAMAN SIKAP SOSIAL SISWA KELAS VIII MELALUI PEMBELAJARAN IPS DI SMP UNGGULAN ZAINUL HASAN GENGGONG - Elmi Mufidah; Eka Rahayu (Madani : Journal of Social Sciences and Social Science Education, 2023)
Based on the results of observations made at Unggulan Middle School, especially in class VIII, there are many students who have not fully internalized social attitudes in the classroom. Some students show a lack of discipline and responsibility, such as often being late for class, lacking focus when the teacher explains, and being involved in inappropriate activities during class hours. The aim of this research is to obtain a description of, first, a description of the social studies learning process carried out by teachers in instilling social attitudes in class VIII students at SMP Unggulan. Second, the results of instilling social attitudes in class VIII students at Unggulan Middle School through social studies learning. The method used is a descriptive qualitative approach.  The sample used in this research was purposive sampling, class VIII.  The data collection techniques used in this research are observation, in-depth interviews, and documentation. Testing the validity of the data in this research uses source triangulation techniques. The results of the analysis that have been found to instill social attitudes through social studies learning in class VIII students at Unggulan Middle School, as well as the results of instilling social attitudes in class VIII students through social studies learning in class VIII students at Unggulan Middle School, have been embedded in the good category, namely by instilling values. students' social attitudes with social studies learning strategies, the teacher's ability to provide examples of good interaction attitudes to students both in the classroom and outside the classroom, linking social studies subject matter with social attitude values, and providing positive sentences containing social attitude values at the beginning of learning. The values of social attitudes in class VIII students at SMP Unggulan have been successfully instilled through social studies learning with various strategies.  The use of social studies learningstrategies is very important for choosing the right social studies learning strategies so that students can more easily understand and apply the values of social attitudes in context. lesson. And evaluations related to social attitudes also play an important role in instilling values. Furthermore, the results of instilling social attitudes in class VIII students at Unggulan Middle School have been successfully achieved in the "Good" category. The teacher succeeded in implementing social attitude values in accordance with the indicators explained by the researchers, such as honesty, manners, discipline and tolerance in class VIII students at Unggulan Middle School.